Studi Kasus Motivasi Kerja dan Kinerja Karyawan Bagian Administrasi Koperasi Universitas Yudharta Pasuruan - Chandra Prasetya Wahyudi; Lumhatus Shofi Sa'adah; Dea Eka Wulandari; Farizky Maulana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to explore the relationship between work motivation and employee performance in the administrative department of the Yudharta University Cooperative in Pasuruan. The research employs a qualitative approach using a case study method. The research informants consist of two employees working in the administrative division. Data were collected through in-depth interviews and direct observation. The results show that high work motivation, both from internal and external factors, has a positive impact on employee performance in terms of punctuality, accuracy, and service quality. These findings reinforce the importance of creating a motivating work environment as an effort to improve employee performance within the cooperative setting.